Formulation of pH-responsive highly swellable hydrogel scaffolds for controlled release of tramadol HCl: characterization and biocompatibility evaluation - Abdullah, Zainab; Ashraf, Muhammad Umer; Barkat, Kashif; Badshah, Syed Faisal; Rehman, Umaira; Razzaq, Asma; Mahmood, Asif; Ulhaq, Farid; Chopra, Hitesh; Rashid, Summya; Valko, Marian; Alomar, Suliman; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
The objective of current project was to formulate a system for controlled delivery of tramadol HCl (TRD), an opioid analgesic used in the treatment of moderate to severe pain. For this purpose, a pH responsive AvT-co-poly (MAA) hydrogel network was formulated through free radical polymerization by incorporating natural polymers i.e., aloe vera gel and tamarind gum, monomer and crosslinker. Formulated hydrogels were loaded with tramadol HCl (TRD) and evaluated for percent drug loading, sol-gel fraction, dynamic and equilibrium swelling, morphological characteristics, structural features and in-vitro release of tramadol HCl. Hydrogels were proved to be pH sensitive as remarkable dynamic swelling response ranging within 2.94g/g-10.81g/g was noticed at pH 7.4 as compared to pH 1.2. Percent drug loading was in the range of 70.28%-90.64% for all formulations. Thermal stability and compatibility of hydrogel components were validated by DSC analysis and FTIR spectroscopy. Controlled release pattern of tramadol HCl from the polymeric network was confirmed as maximum release of 92.22% was observed for over a period of 24 hours at pH 7.4. Moreover, oral toxicity studies were also conducted in rabbits to investigate the safety of hydrogels. No evidence of any toxicity, lesions and degeneration was reported, confirming the biocompatibility and safety of grafted system.